The night ship : a novel - Kidd, Jess (New York : Atria Books, 2022)
"1629: A newly orphaned young girl named Mayken is bound for the Dutch East Indies on the Batavia, one of the greatest ships of the Dutch Golden Age. Curious and mischievous, Mayken spends the long journey going on misadventures above and below the deck, searching for a mythical monster. But the true monsters might be closer than she thinks. 1989: A lonely boy named Gil is sent to live off the coast of Western Australia among the seasonal fishing community where his late mother once resided. There, on the tiny reef-shrouded island, he discovers the story of an infamous shipwreck." -- Dust jacket.
Keywords: Batavia (Ship) -- Fiction; Shipwrecks -- Fiction; Orphans -- Fiction; Mothers -- Death -- Fiction; Secrecy -- Fiction; Folklore -- Fiction; Fate and fatalism -- Fiction; Passenger ships -- Fiction; Children -- Fiction; Shipwrecks -- Australia -- Fiction; Western Australia -- Fiction; Western Australia -- History -- Fiction; Historical fiction